Application of Fishbone and FMEA in Quality Control of Tempe Production at Batujajar UMKM - Billah, Anggita Salsa; Sari, Rini Mulyani (Darul Yasin Al Sys, 2025)
This study addresses the limited application of structured quality control tools in traditional food production, particularly within small and medium-sized enterprises (SMEs) such as tempe producers, despite their importance for product consistency and consumer satisfaction. The research aims to identify and analyze the dominant factors contributing to product defects, with a specific focus on discoloration in tempe production, using the Fishbone Diagram and Failure Mode and Effects Analysis (FMEA) as analytical frameworks. Adopting a qualitative-descriptive case study design, one tempe-producing SME in Batujajar was purposively selected. Data were collected through field observations and in-depth interviews over four months (March–June 2025) and supported by defect records from January to September 2024. Findings indicate that the primary cause of discoloration is insufficient employee training, followed by inconsistent implementation of standard operating procedures (SOPs), inadequate temperature and humidity control, poor yeast storage, and environmental conditions. FMEA results show that human error due to lack of training had the highest Risk Priority Number (RPN = 288), marking it as the most critical failure mode. The study concludes that preventive solutions such as regular training, SOP standardization, and environmental monitoring are essential for improving tempe product quality. The implications extend to theoretical contributions in quality management within the informal food sector and practical recommendations for SMEs and policymakers to adopt low-cost, effective quality control strategies. Future research should explore the long-term effects of such interventions on business sustainability and customer satisfaction in small-scale food enterprises.